Preparation of Titanium Dioxide (TiO2) from Waste of Polymetallic Ore Processing via Sulfurization Treatment - Otgon-Uul, Enkh-Uyanga; Baatar, Munkhtsetseg; Nanzad, Ulziijargal; Lkhamsuren, Jargalsaikhan (Indonesian Journal of Chemistry, 2024)
Various experimental conditions were applied to extract titanium oxide from the waste of polymetallic ore. X-ray diffraction (XRD) analysis confirms that the waste of polymetallic ore contains including various minerals such as almandine (Fe,Mg,Ca)3Al2Si3O12, brownmillerite (FeAlO3(CaO)2), quartz (SiO2), magnetite (Fe3O4). Using H2SO4 acid with a concentration of 93% in the S/L mass ratio of 1:1.5 at 140 °C is suggested as an optimum reaction condition. Its hydrolysis subsequently leads to the formation of the titanyl sulfate (TiOSO4), and relatively pure titanium oxide is obtained through precipitation and calcination at 600 °C. The observed band gap value of 3.2 eV for the obtained TiO2 corresponds to the typical band gap value of anatase-type TiO2. We calculated the crystallite size of extracted anatase-type titanium oxide according to the Debye-Scherrer equation it was determined to be 96.35 nm. Fully reflecting X-ray fluorescence (XRF) determined that the purity of extracted TiO2 is 93.18%. This report presents a newly developed process that enables the production of relatively high-purity TiO2 (93.18%) from the waste of polymetallic ore (TiO2 5.39%) by a simple sulfurization process.